Obowiązywanie reguły ignorantia iuris nocet w odniesieniu do cudzoziemców - Płachta, Michał (Wydział Prawa i Administracji UAM, 1986)
In relation to the international personal traffic and tourism there are situations encountered in penal proceedings when defendants are pleading ignorance of the Polish penal law, on top of it, in some cases the ignorance is also fostered by different socio-cultural conditions, system of moral norms and ethical values. According to the ancient Roman principle everyone, including also aliens, must know the penal law, thus ignorance of the law cannot be treated as a circumstance precluding a penal responsibility. Yet, the aliens find themselves in much worse situations then the (locals, a question thus anises whether they could be offered more „priviledged" treatment in the context of the „ignorantia iuris nocet" principle. Art. 24 par. 2 of the Penal Code proclaims that ignorance of illegality of act cannot preclude penal responsibility under condition that a perpetrator was able to avoid his error. If he was able to avoid his ignorance as to illegality, and committed an intentional offence, then the court may apply the extraordinary mitigation of they of the penalty (par. 3). If an allien-defendant explains committing his unlawful act by a custom adopted in his home society the Polish courts cannot take it as a circumstance excluding penal responsibility in principle, nor as mitigating it- contrary to the British jurisdictions, according to which a court may renounce of inflicting a punishment. The effect of ignorance of the law exhibited by aliens ought to be discussed against the background of the division of offences into: mala in są and mala prohibita. The author advocates that the ignorantia iuris is legally irrelevant in relation to the first group offences, but it has to be considered in case of certain offences of the second group.
Validity of the rule ignorantia iuris nocet with regards to aliens